Higher Learning During COVID-19: Reflections on Spaces and Flows of the New Normal (Comparative & International Education Series, 2021)
In the winter-spring semester of 2020, the deadly COVID-19 pandemic brought the academic world to a halt. Between February 13 and August 4, 2020, the influential global edition of University World News featured 666 articles about the drama: “Universities cancel graduation ceremonies due to virus” (13.02); “Science has been placed on hold in face of coronavirus” (18.02); “Virus-related closures disrupt university entrance exams” (27.02); “Coronavirus restrictions affect cross-border research” (13.03); “Contact learning in universities suspended, students sent home” (16.03); “Returning students add to new spike in coronavirus cases” (18.03); “International students struggle under containment measures” (20.03); “Who will field the cost of conference cancellations?” (21.03); “Thesis defence goes online as universities remain closed” (21.03); “Turn to online learning shows varying degrees of readiness” (26.03); “Five years to recover global mobility, says IHE expert” (26.03); “Students demand crisis support in grants, not loans” (30.03);  “COVID-19 raises families’ anxiety over abducted students” (30.03); “Students go on unprecedented online strikes for equality” (03.04); “Post-pandemic outlook for HE is bleakest for the poorest” (4.04); “Several institutions announce faculty hiring freezes” (04.04); “After COVID-19, nothing will be the same” (06.04); “Early-career scientists brace for impact of COVID-19” (11.04), “Universities asked to set up student mental health helplines” (11.04); “Students fall victim to a war against all Africans” (14.04); “Civility and unity are needed, not racism” (23.04). This constitutes a mere selection of headlines published in one academic news outlet alone.